The Impact of Metabolic Syndrome and Obesity on the Evolution of Diastolic Dysfunction in Apparently Healthy Patients Suffering from Post-COVID-19 Syndrome - Cristina Tudoran; Mariana Tudoran; Talida Georgiana Cut; Voichita Elena Lazureanu; Felix Bende; Renata Fofiu; Alexandra Enache; Silvius Alexandru Pescariu; Dorin Novacescu (Biomedicines, 2022)
(1) Background: Coronavirus disease 2019 (COVID-19) has a worse prognosis in individuals with obesity and metabolic syndrome (MS), who often develop cardiovascular complications that last throughout recovery. (2) Methods: This study aimed to analyze the evolution of diastolic dysfunction (DD), assessed by transthoracic echocardiography (TTE), in 203 individuals with and without obesity and/or MS diagnosed with post-COVID-19 syndrome. (3) Results: DD was frequently diagnosed in patients with MS and obesity, but also in those without obesity (62.71% and 56.6%, respectively), in comparison to 21.97% of subjects without MS (p ˂ 0.001). Almost half of the patients with obesity and MS had more severe DD (types 2 and 3). As for evolution, the prevalence and severity of DD, particularly types 1 and 2, decreased gradually, in parallel with the improvement of symptoms, progress being more evident in subjects without MS. DD of type 3 did not show a significant reduction (p = 0.47), suggesting irreversible myocardial damages. Multivariate regression analysis indicated that the number of MS factors, the severity of initial pulmonary injury, and protein C levels could explain DD evolution. (4) Conclusions: DD was commonly diagnosed in individuals with post-COVID-19 syndrome, particularly in those with MS and obesity. After 6 months, DD evolution, excepting that of type 3, showed a significant improvement, mostly in patients without MS.